COMPARATIVE ANALYSIS OF THE BENEFITS AND DIFFICULTIES OF OBSTETRIC PSYCHOPROPHYLAXIS, IN PREGNANT WOMEN OF THE HEALTH CENTERS OF CUMANDÁ AND CERECITA - ECUADOR - Morales, Vicky Narea; Nader, Jorge Daher; Rodríguez, Katherine; Baño, Cinthya; Jiménez, Gabriel (International Journal of Research -GRANTHAALAYAH, 2020)
The woman who is in a state of gestation tends to create fears implanted by rumors of society about labor, the main fear is the pain caused by labor. Only through a comprehensive, adequate, timely preparation will favorable results be achieved; by obstetric psychoprophylaxis. The research was carried out in two Health Centers in different regions of Ecuador. The Cerecita health center is located in the Cerecita enclosure, Guayaquil canton, Guayas province and the Cumandá health center which is located in the Cumandá canton within the Chimborazo province. This research work corresponds to a descriptive, analytical, non-experimental, cross-sectional study, with a correlational design. The sample consists of 198 pregnant women from the health centers of Cerecita (94) and Cumandá (104) Ecuador, nulliparous and multiparous who attended sessions of Obstetric Psychoprophylaxis that met the inclusion and exclusion criteria. The results obtained were: in the age range in which the pregnant women were from the study carried out was between 14 and 19 years with a total of 95 patients, the attitude to practice psychoprophylaxis (PPO) with 102 patients performed Between 3 and 4 sessions, in the hours of labor the largest number with a total of 98 pregnant women were between 5 to 7 hours in this period, while 100 had a low pain threshold. Of the study group 159 pregnant women were eutocic births, the pregnant women of the Cumandá health center presented difficulties in attending the obstetric psychoprophylaxis sessions.